HUBUNGAN PRAKTIK MENYIKAT GIGI DENGAN DEBRIS INDEX SISWA TUNAGRAHITA DI SLB B-C OPTIMAL SURABAYA - Arifian, Ersa; Chairanna, Ida; Prasetyowati, Silvi (Jurnal Skala Kesehatan, 2022)
Abstract: Debris index is a value or score of soft deposits attached to the tooth surface. Plaque and debris can be cleaned by brushing your teeth, but in just a few minutes a thin film of saliva will form, then the germs in the saliva will stick together with the rest of the food to form deposits that become debris. The problem in this study is the high percentage of debris index of mentally retarded students at SLB B-C Optimal Surabaya in 2022 (60.6%). How to brush your teeth must be correct so that all remaining food in the oral cavity can be cleaned optimally. The wrong and less effective way of brushing teeth will affect the dental and oral hygiene status (debris index) to be bad, so that in maintaining dental and oral hygiene, it is necessary to pay attention to good and correct brushing practices. This study aims to determine the relationship between tooth brushing practice and the debris index of mentally retarded students at SLB B-C Optimal Surabaya. Research method, This type of research is analytical research. The respondents in this study were 33 mentally retarded students. The data collection method was by examination and observation. The data analysis technique used the kendall tau-b correlation test. The results of the study were that there was a significant relationship between tooth brushing practice and the debris index of mentally retarded students at SLB B-C Optimal Surabaya. Keywords: Toothbrushing Practice, Debris Index, Children with Mental Requirements